1990
DOI: 10.1111/j.1365-2672.1990.tb01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of ‘obiolor’: a Nigerian fermented non‐alcoholic beverage

Abstract: Obiolor is an acidic non-alcoholic beverage prepared by fermenting sorghum and millet malts. The traditional process for the production and microbiological characteristics of the beverage were investigated. Bacillus spp., Lactobacillus plantarum and Streptococcus lactis were the associated micro-organisms most actively involved. Yeasts were present in low numbers towards the end of the fermentation. Other micro-organisms isolated did not appear to play a role in the fermentation process. Variations in the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…Faparusi et al [18] found the presence of contaminants in the various stages of burukutu liquor production (a locally made alcoholic beverage from millet) and indicated that most of the bacteria survived at low acidity. This observation had been confirmed by other researchers [19][20]. S. cerevisiae which appeared in all the sites could be the predominant fermenter while most of the other microorganisms were there as opportunistic and contaminants from the environment.…”
Section: Lactobacillus Plantarum Lsupporting
confidence: 85%
See 1 more Smart Citation
“…Faparusi et al [18] found the presence of contaminants in the various stages of burukutu liquor production (a locally made alcoholic beverage from millet) and indicated that most of the bacteria survived at low acidity. This observation had been confirmed by other researchers [19][20]. S. cerevisiae which appeared in all the sites could be the predominant fermenter while most of the other microorganisms were there as opportunistic and contaminants from the environment.…”
Section: Lactobacillus Plantarum Lsupporting
confidence: 85%
“…Spoilage microbes in olewonyo A range of microbes can be associated with olewonyo production, but only a few may be able to cause spoilage. As microbes differ in their growth requirements, different beverages support different spoilage microorganisms [14][15][16][17][18][19][20][21][22][23]. Lactic and acetic acid bacteria are the most common spoilage bacteria found in soft drinks.…”
Section: Lactobacillus Plantarum Lmentioning
confidence: 99%
“…1995), millet (Efiuvwevwere and Akona 1995; Zvauya et al . 1997; Lei and Jakobsen 2004) and sorghum (Odunfa and Adeyele 1985; Achi 1990; Nout 1991; Sulma et al . 1991; Gassem 1999; Kunene et al .…”
Section: Discussionmentioning
confidence: 99%
“…Obiolor is a non‐alcoholic beverage produced from fermented sorghum and millet malts in Nigeria, where it is consumed on a daily basis by the Igala tribe and is closely associated with good health. The sweet taste of this gruel is attributed to sorghum and millet malt . Lactobacillus plantarum and Lactococcus lactis are responsible for the acidity, taste and aroma of the end product.…”
Section: Introductionmentioning
confidence: 99%